Monitoring the growth of social and emotional competence to guide practice decisions - Valerie B. Shapiro; Bo-Kyung Elizabeth Kim; Jennifer L. Robitaille; Joseph L. Mahoney; Juyeon Lee; Paul A. LeBuffe (Social and Emotional Learning: Research, Practice, and Policy)
To facilitate social and emotional learning (SEL) in schools, assessments must be suitable for progress monitoring, which includes being sensitive to short-term changes in students’ social and emotional competence (SEC) and providing useful and timely information to educators. This paper discusses evidence criteria to help determine whether an instrument is suitable for progress monitoring of student SEC. To illustrate how action-oriented research can help further guide the development of evidence standards and inform SEL practice in schools, the Devereux Student Strengths Assessment-mini (DESSA-mini) is highlighted through two empirical case studies. Data for both case studies are derived from a district-wide implementation of an evidence-based SEL program, Promoting Alternative THinking Strategies (PATHS), that used the DESSA-mini to assess the SEC of 7681 students in Grades K-5 at three time points over a school year. Multilevel models estimated the growth in student SEC under different implementation conditions and by different student characteristics (i.e., grade, gender, SEC at baseline). Findings suggest significant growth in SEC with some meaningful variation. Results are interpreted to illustrate how routine-practice studies can be used to infer how much growth is typical, among which students, and under what conditions, to facilitate real-time practice decisions. Impact Statement: To facilitate social and emotional learning in schools, educators need to monitor progress in students’ acquisition of social and emotional competence. Two case studies are presented to illustrate how studies can be used to infer how much growth is typical, among which students, and under what conditions, to facilitate real-time decisions by educators to adjust instruction.